The 2009 tennis anti-doping programme - Miller, S. (Medicine and Science in Tennis, 2009)
The introduction of a revised WADA Code has required changes to the Tennis Anti-Doping Programme (TADP) to ensure that the latter remains compliant. This article summarizes some key changes to the TADP for 2009 (whereabouts, therapeutic use exemptions, testing, provisional suspension, doping offences, sanctions, costs, retirement, status during ineligibility, communicating the changes).